PEMIKIRAN EKONOMI AL-GHAZALI - Fahlefi, Rizal (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2012)
According to al-Ghazali, the goal of life of a moslem is reach the Allah blessing (ridha) both in world and the world after. One of the media that facilitate the achievement of the goal is legal wealth (halal) in economic activities. For al-Ghazali, market is believed to a an evolution of “law of nature”, that is, the passion coming from inside of someone to fulfill each other’s economic need. With his evolution theory about money, al -Ghazali explains that the there have been a shift from barter system to money-based economic system. Money, according to him, may bring two possible things to human, good or bad, depending how individuals use it.